Handbook of Cyber-Development, Cyber-Democracy, and Cyber-Defense (Springer International Publishing, 2018)
This volume covers a wide spectrum of issues relating to economic and political development enabled by information and communication technology (ICT). Showcasing contributions from researchers, industry leaders, and policymakers, this Handbook provides a comprehensive overview of the challenges and opportunities created by technological innovations that are profoundly affecting the dynamics of economic growth, promotion of democratic principles, and the protection of individual, national, and regional rights. Of particular interest is the influence of ICT on the generation and dissemination of knowledge, which, in turn, empowers citizens and accelerates change across all strata of society. Each essay features literature reviews and key references; definition of critical terms and concepts, case examples; implications for practice, policy, and theory; and discussion of future directions. Representing such fields as management, political science, economics, law, psychology, and education, the authors cover such timely topics as health care, energy and environmental policy, banking and finance, disaster recovery, investment in research and development, homeland security, and diplomacy in the context of ICT and its economic, political, and social impact.